Green agriculture cultivation of groundnut (Arachis hypogaea) with foliar applied plant leaf extract and soil applied panchgavya - KUMAWAT, R N; MAHAJAN, S S; MERTIA, R S; MEENA, O P (The Indian Journal of Agricultural Sciences, 2012)
The effect of soil applied panchgavya and foliar applied plant leaf extracts on the biochemical properties, yield and yield attributes of groundnut (Arachis hypogaea L.) was examined in a field trial at CAZRI, Regional Research Station, Jaisalmer during kharif 2006 and 2007 under irrigated conditions. Successive increase in panchgavya levels from 0 to 3.0 l/m2 led to significant increase in dry matter, chlorophyll content, nitrate reductase activity, yield and yield attributes of groundnut. Soil application of panchgavya at 3.0 l/m2 recorded 85, 93 and 90% higher pod, haulm and biological yield compared to control. Foliar application of neem (Azadirachta indica), datura (Datura metel) and tumba (Citrullus colocynthis) plant leaf extracts in combination with Panchgavya in 1: 1 ratio at 35 and 55 days after sowing recorded significantly higher content of chlorophyll, plant dry matter, yield attributes and pod yields compared to water sprayed control. Foliar application of datura + panchgavya recorded 22 and 21% higher pod and biological yields compared to water sprayed control.